Partial current information and signal extraction in a rational expectations macroeconomic model: A computational solution - Laurian Lungu; Kent Matthews; Patrick Minford (Cardiff University, Cardiff Business School, 2006)
Previous attempts at modelling current observed endogenous financial variables in a macroeconomic model have concentrated on only one observed endogenous variable – namely the short-term rate of interest. The solution method for dealing with more than one observed endogenous variable has thus far been computationally intractable. This paper applies a general search algorithm to a macroeconomic model with an observed interest rate and exchange rate to solve the signal extraction problem. The informational advantage of applying the signal extraction algorithm to all the current observed endogenous variables is examined in terms of the implication for policy from the misperceptions of specific macroeconomic shocks.
Keywords: E37; 330; Rational Expectations; Partial Current Information; Signal Extraction; Macroeconomic modelling